PENYINTAS KEKERASAN SEKSUAL DALAM FILM PENYALIN CAHAYA - Maudhy Sukma Permatasari; Diana Amalia (Universitas Garut, 2022)
Abstract Film is a medium of communication that has great ability and power. Besides being used as a medium of entertainment, films are also used as a medium for public education. This makes the film as an effective communication medium to convey messages with a specific purpose. Film Cahaya aims to raise the issue of sexual violence, especially cases in universities. Copy of Cahaya tells the story of a student's struggle in seeking justice for the case of her drunken photo that was spread. This film is full of signs and symbols in describing the figure of Suryani as a survivor of sexual violence. This study aims to explain the representation of survivors of sexual violence in the film Pengalin Cahaya. This study uses a qualitative method through the semiotic approach of Roland Barthes, it can be seen the meaning of denotation, connotation, and myths related to the depiction of survivors of sexual violence. The number of corpus in this research is 7 scenes that depict the figure of survivors of sexual violence. The results of this study indicate that survivors of sexual violence in the film Pengalin Cahaya are described as subordinate individuals. The signs and symbols in this film show that survivors of sexual violence are figures who have low power so that they have limitations in decisions and actions taken. Survivors of sexual violence in the film Pengalin Cahaya in a denotative sense are a sign that survivors of sexual violence do not get help and are made the wrong party. The victim was forced to make peace and make a clarification video to recover the name of the perpetrator. In the end, the victim felt disappointed with the situation. Keywords: Film; survivor; sexual violence; semiotics. Â AbstrakFilm merupakan media komunikasi yang memiliki kemampuan dan kekuatan yang besar. Selain digunakan sebagai media hiburan, film juga digunakan sebagai media edukasi masyarakat. Hal tersebut menjadikan film sebagai media komunikasi yang efektif untuk menyampaikan pesan dengan tujuan tertentu. Film Cahaya bertujuan untuk mengangkat isu kekerasan seksual, terutama kasus di perguruan tinggi. Penyalin Cahaya menceritakan tentang perjuangan seorang mahasiswi dalam mencari keadilan atas kasus foto mabuknya yang tersebar. Film ini sarat akan tanda dan lambang dalam menggambarkan sosok Suryani sebagai penyintas kekerasan seksual. Penelitian ini bertujuan untuk menjelaskanÂ representasi penyintas kekerasan seksual dalam film Penyalin Cahaya. Penelitian ini menggunakan metode kualitatif melalui pendekatan semiotika Roland Barthes, dapat diketahui makna denotasi, konotasi, dan mitos yang berkaitan dengan penggambaran sosok penyintas kekerasan seksual. Jumlah koprus pada penelitian kali ini adalah 7 scene yang menunjukkan penggambaran sosok penyintas kekerasan seksual. Hasil penelitian ini menunjukkan bahwa penyintas kekerasan seksual pada film Penyalin Cahaya digambarkan sebagai individu subordinat. Tanda dan lambang pada film ini menunjukkan bahwa penyintas kekerasan seksual merupakan sosok yang memiliki kekuasaan rendah sehingga memiliki keterbatasan dalam keputusan dan tindakan yang diambil. Penyintas kekerasan seksual dalam film Penyalin Cahaya dalam makna denotasi adalah penanda bahwa penyintas kekerasan seksual tidak mendapat bantuan dan dijadikan pihak yang salah. Korban terpaksa harus berdamai dan membuat video klarifikasi untuk memulihkan nama pelaku. Pada akhirnya, korban merasa kecewa dengan keadaan.Kata-kata kunci: Film; penyintas; kekerasan seksual; semiotika.